Within-host dynamics of antiviral treatment with remdesivir for SARS-CoV-2 infection - Schuh, Lea; Markov, Peter V.; Voulgaridi, Ioanna; Bogogiannidou, Zacharoula; Mouchtouri, Varvara A.; Hadjichristodoulou, Christos; Stilianakis, Nikolaos I. (Journal of the Royal Society Interface, 2024)
The effectiveness of antiviral treatment with remdesivir against COVID-19 has been investigated in clinical trials suggesting earlier recovery. However, this effect seems to be rather modest. In this study, we tracked the clinical course of SARS-CoV-2 infections in 369 COVID-19 individuals across a spectrum of illness severities, including both untreated individuals and individuals who received antiviral treatment with remdesivir. Moreover, using a process-based mathematical model, we quantified and analysed the within-host infection dynamics of a total of 88 individuals, of which 69 were untreated and 19 antiviral-treated individuals. For untreated individuals, we found that those hospitalized exhibit lower levels of early immune response and higher cumulative viral loads than those who were not. For treated individuals, we found that those who died were on average hospitalized later after symptom onset than those who survived, underscoring the importance of early medical intervention for severe COVID-19. Finally, our model estimates a rather limited antiviral activity of remdesivir. Our results provide valuable insights into the clinical course of COVID-19 during antiviral treatment with remdesivir and suggest the need for alternative treatment regimens.
CRIS-Team Scopus Importer:2025-02-04
Keywords: antiviral treatment; COVID-19; infectious disease modelling; mechanistic model; viral kinetics